2014
DOI: 10.1039/c3dt53280a
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic conformation of a cerocene [Ce(COT′′)2] exhibiting a uniconfigurational f1 ground state and slow-magnetic relaxation

Abstract: Magnet-like behaviour, in the form of slow relaxation of the magnetization, was observed for a monometallic cerium(III) sandwich complex. The use of trimethylsilyl substituted COT ligands (COT'') led to the formation of a staggered COT'' arrangement in the cerocene-type sandwich complex with a well-defined oxidation state of +3 for the Ce ion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 32 publications
1
52
1
Order By: Relevance
“…The molecular structures of Tm 2 @C s (6)-C 82 and Tm 2 C 2 @C s (6)-C 82 have been determined by means of single-crystal X-ray diffraction using co-crystals with nickel octaethylporphyrin (Ni(OEP)). It was found that the relative metal positions of Tm@C s (6)-C 82 , Tm 2 @(I)-C82 and Tm 2 C 2 @(I)-C 82 are similar, and the Tm positions are slightly shifted off-center by the encapsulation of additional Tm and C atoms. The molecular orientations of Tm@C s (6)-C 82 , Tm 2 @(I)-C82 and Tm 2 C 2 @(I)-C 82 relative to Ni(OEP) were also found to be similar with each other.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…The molecular structures of Tm 2 @C s (6)-C 82 and Tm 2 C 2 @C s (6)-C 82 have been determined by means of single-crystal X-ray diffraction using co-crystals with nickel octaethylporphyrin (Ni(OEP)). It was found that the relative metal positions of Tm@C s (6)-C 82 , Tm 2 @(I)-C82 and Tm 2 C 2 @(I)-C 82 are similar, and the Tm positions are slightly shifted off-center by the encapsulation of additional Tm and C atoms. The molecular orientations of Tm@C s (6)-C 82 , Tm 2 @(I)-C82 and Tm 2 C 2 @(I)-C 82 relative to Ni(OEP) were also found to be similar with each other.…”
mentioning
confidence: 94%
“…It was found that the relative metal positions of Tm@C s (6)-C 82 , Tm 2 @(I)-C82 and Tm 2 C 2 @(I)-C 82 are similar, and the Tm positions are slightly shifted off-center by the encapsulation of additional Tm and C atoms. The molecular orientations of Tm@C s (6)-C 82 , Tm 2 @(I)-C82 and Tm 2 C 2 @(I)-C 82 relative to Ni(OEP) were also found to be similar with each other. These facts demonstrated that the stable endohedral Tm positions are not fundamentally affected by the addition of the other Tm atoms but dependent on the kind of the fullerene cage structure.…”
mentioning
confidence: 94%
See 3 more Smart Citations